Adherence to CONSORT adverse event reporting guidelines in randomized clinical trials evaluating systemic cancer therapy: a systematic review - Péron, Julien; Maillet, Denis; Gan, Hui K; Chen, Eric X; You, Benoit (Journal of clinical oncology, 2013)
The Consolidated Standards of Reporting Trials (CONSORT) guidance was extended in 2004 to provide a set of 10 specific and comprehensive guidelines regarding adverse event (AE) reporting in randomized clinical trials (RCTs). Limited data exist regarding adherence to these guidelines in publications of oncology RCTs. All phase III RCTs published between 2007 and 2011 were reviewed using a 16-point AE reporting quality score (AERQS) based on the 2004 CONSORT extension. Multivariable linear regression was used to identify features associated with improved reporting quality. A total of 325 RCTs were reviewed. The mean AERQS was 10.1 on a 16-point scale. The most common items that were poorly reported were the methodology of AE collection (adequately reported in only 10% of studies), the description of AE characteristics leading to withdrawals (15%), and whether AEs are attributed to trial interventions (38%). Even when reported, the methods of AE collection and analysis were highly heterogeneous. The multivariable regression model revealed that industry funding, intercontinental trials, and trials in the metastatic setting were predictors of higher AERQS. The quality of AE reporting did not improve significantly over time and was not better among articles published in journals with a high impact factor. Our findings show that some methodologic aspects of AE collection and analysis were poorly reported. Given the importance of AEs in evaluating new treatments, authors should be encouraged to adhere to the 2004 CONSORT guidelines regarding AE reporting.